The Dialectics of Islamic Law and Customary Law in Resolving Digital Cultural Grievances: A Case Study of Pandji Pragiwaksono’s Customary Sanctions in Tana Toraja - Ahmad Faizal Adha; Fahmi Fatwa Rosyadi Satria Hamdani; Liana Abia Fatimah (Universitas Islam Sultan Agung, 2026)
This study aims to analyze the legal construction and dialectical interaction between Islamic law and customary law in resolving digital cultural grievances in Indonesia's pluralistic legal system. It focuses on the landmark case of comedian Pandji Pragiwaksono, who was subjected to Torajan customary sanctions in 2026 for digital comedy content produced in 2013. The research employs a qualitative normative juridical method utilizing case, conceptual, and statutory approaches. The results reveal that digital cultural offenses can be theoretically reconstructed as Jarimah Ta'zir, as the permanent nature of digital footprints satisfies the formal, material (al-rukn al-maddi), and moral (al-rukn al-adabi) elements of a discretionary offense that degrades communal dignity (al-ihanah). Furthermore, the study demonstrates that the Torajan customary sanction of one pig and five chickens within the Massarrin ritual possesses structural harmony with the Islamic principles of Islah (reconciliation) and Maslahah Mursalah, prioritizing the restoration of social equilibrium and protection of honor (Hifdz al-'Ird) over rigid retributive state punishments. Ultimately, this research provides a conceptual hybrid model of living law-based restorative justice, offering critical practical and theoretical insights for law enforcement and judicial alignment under the framework of the New Indonesian Criminal Code (Law No. 1 of 2023).